Transcutaneous Vagus Nerve Stimulation: Retrospective Assessment of Cardiac Safety in a Pilot Study - Kreuzer, Peter M.; Landgrebe, Michael; Husser, Oliver; Resch, Markus; Schecklmann, Martin; Geisreiter, Florian; Poeppl, Timm B.; Prasser, Sarah J.; Hajak, Goeran; Langguth, Berthold (Frontiers in Psychiatry, 2012)
Abstract BACKGROUND: Vagus nerve stimulation has been successfully used as a treatment strategy for epilepsy and affective disorders for years. Transcutaneous vagus nerve stimulation (tVNS) is a new non-invasive method to stimulate the vagus nerve, which has been shown to modulate neuronal activity in distinct brain areas. OBJECTIVES: Here we report effects of tVNS on cardiac function from a pilot study, which was conducted to evaluate the feasibility and safety of tVNS for the treatment of chronic tinnitus. METHODS: Twenty-four patients with chronic tinnitus underwent treatment with tVNS over 3 to 10 weeks in an open single-armed pilot study. Safety criteria and practical usability of the neurostimulating device were to investigate by clinical examination and electrocardiography at baseline and at several visits during and after tVNS treatment (week 2, 4, 8, 16 and 24). RESULTS: Two adverse cardiac events (one classified as a severe adverse event) were registered but considered very unlikely to have been caused by the tVNS device. Retrospective analyses of electrocardiographic parameters revealed a trend towards shortening of the QRS complex after tVNS. CONCLUSION: To our knowledge this is one of the first studies investigating feasibility and safety of tVNS in a clinical sample. In those subjects with no known pre-existing cardiac pathology, preliminary data do not indicate arrhythmic effects of tVNS.